Quantitative Evaluation of the Competing Effects of Wastewater Disposal and Hydraulic Fracturing on Causing Induced Earthquakes: A Case Study of an M3.1 Earthquake Sequence in Western Canada. Issue 2 (4th February 2023) - Wang, Bei; Kao, Honn; Yu, Hongyu; Visser, Ryan; Verdecchia, Alessandro
Abstract: Previous studies mainly attribute injection‐induced earthquakes (IIE) to hydraulic fracturing (HF) operations in the Western Canada Sedimentary Basin (WCSB), whereas the role of wastewater disposal (WD) has been largely overlooked. One particular reason is that HF operations usually exhibit a clearer spatiotemporal relationship to IIE than WD. However, ignoring the effects from WD when investigating the seismogenisis of IIE in the WCSB may not be appropriate, especially when both types of injection activities are present in the vicinity of the epicentral area. Here, we conduct a case study on an M3.1 earthquake sequence located in the WCSB that can be spatiotemporally correlated with both active HF and WD operations. We first build an enhanced catalog consisting of 256 events to delineate the relationship between the occurrence of IIE and injection history. We then investigate the source parameters of the mainshock in detail. Finally, we build a numerical model to calculate the Coulomb stress change caused by each type of injections on the two nodal planes of the derived focal mechanism. The result suggests that the M3.1 event probably occurred on a near‐horizontal nodal plane. In addition, the pore pressure diffusion from WD and the poroelastic stress transfer from HF could work collaboratively to cause an IIE. Therefore, stress perturbation caused by long‐term WD should also be considered in the seismogenic process of an IIE, especially when both active HF and WD are in the immediate vicinity of the IIE. Plain Language Summary: Can we distinguish the roles of different types of injections, that is, hydraulic fracturing (HF) and wastewater disposal (WD), on inducing a particular injection‐induced earthquake (IIE) sequence? In the past, studies use spatiotemporal criteria to associate earthquakes to the closest injection activity. However, there were no quantitative analysis to verify if such a practice is adequate. To help better understand this problem, we conduct a case study focusing on an M3.1 IIE sequence in northeastern British Columbia, which occurred in the vicinity of both active HF and WD injections in 2017. We quantitatively investigate the roles played by different types of injections and how the geomechanical effects contribute to its occurrence. We find that both types of injections could contribute to the triggering process, but with different time scale. WD could slowly bring the preexisting faults to a more stressed state via years of injection. In contrast, HF operations seem to be more directly correlated to the occurrence of IIE, by exerting relative larger stress perturbation to the preexisting fault structures within a much short time period. Therefore, it is probably more appropriate to jointly consider their contributions to the occurrence of IIE when both active WD and HF injections are present nearby. Key Points: In western Canada, wastewater disposal injections and hydraulic fracturing operations may jointly contribute to the occurrences of injection‐induced earthquakes (IIE) The geomechanical analysis from numerical simulation could help determine the true fault plane in scenarios of moderate size IIE A strategy is proposed to numerically estimate the roles of two types of injections presented in the vicinity of the epicentral area